MODEL OF INNOVATIVE STRATEGY ON THE BASIS OF VARIATIVE APPROACH TO PRESCHOOL EDUCATION (Conference Zone, 2021)
This article is based on an innovative strategy model based on a varied approach to preschool education and the curriculum of the subject "Theory and methods of physical education for preschool children." forms of organization of physical education, physical education classes, movement games, sports games and training issues are widely covered.